Sediment accretion in the Mangrove forests of Bebar River, Pahang, Malaysia: 230th concentration versus artificial marker method - Kamaruzzaman, B. Y.; Leong, H.F.; Mohd. Lokman, Hussain; Sulong, Ibrahim; Mohammed Misbahul, Amin (University of Malaya Maritime Research Centre, 2009)
Mangrove forests are a buffer zone between the coast and the ocean. These tropical coastal areas are responsible for about 75% of the sediment discharged from land to sea. Mangrove ecosystem can act as an efficient sediment trap which are dominantly supplied by rivers and the atmosphere to the oceans. In this study, an artificial marker horizon method and a 230Thexcess method were used for the determination of the sedimentation rate in the mangrove forests of Bebar river, Pahang. The determination of the average sedimentation rate is based on the assumption that the 230Thexcess is incorporated into the sediments with a constant rate. The latter method is based on measuring the thickness of a vertical sediment section divided by the time span necessary for its deposition. The result of the sedimentation rate obtained from both methods (0.53 cm-yf1 and 0.54 cm-yr') are mutually consistent. Even though our values are somewhat higher, they are nevertheless comparable to sedimentation rates reported at other intertidal areas. This finding suggests that the mangrove forests are not just passive colonizers of mud banks, but actively capture mud to create their own environments. Mangroves are thus an important sink for the fine sediment from rivers and coastal waters.